English students' perceptions of Automated Writing Evaluation (AWE) in writing engagement at the university level - Pratama, Krisna Deva; Irawati, Tatik (Universitas Merdeka Malang, 2024)
The background of this study is the development of AI in the digital era, specifically AWE, which is currently very popular among universities and has many benefits in student writing. This study investigates how university-level English students' perceptions of AWE influence their engagement in the academic writing process. This research employs a qualitative case study. The participants were 27 students of Argumentative Writing 2022 in the Faculty of Teacher Training and Education, Department of English Education, Universitas PGRI Jombang. The instruments utilized to collect the data are observation and Questionnaires. The data analysis technique models Miles and Huberman include; data condensation, data display, and conclusion. The data analysis shows that this study contributes to understanding English students' perception of how AWE tools influence writing engagement, towards technology-automated writing evaluation, and the potential benefits and challenges associated with the integration of AWE at the university level. The result AWE tools have a positive perception of students at the University level, showing that students benefited from the feedback provided by AWE.Â